2011
DOI: 10.1021/nn102002x
|View full text |Cite
|
Sign up to set email alerts
|

How Isolated Are the Electronic States of the Core in Core/Shell Nanoparticles?

Abstract: We investigated how isolated are the electronic states of the core in a core-shell (c/s) nanoparticles (NPs) from the surface, when the particles are self-assembled on Au substrates via a dithiol (DT) organic linker. Applying photoemission spectroscopy the electronic states of CdSe core only and CdSe/ZnS c/s NPs were compared. The results indicate that in the c/s NPs the HOMO interacts strongly with electronic states in the Au substrate and is pinned at the same energies, relative to the Fermi level, as the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…MT linkers were found to quench the PL signal by about 75%, and the quenching was independent of the linker length. This effect is well known for CdSe NPs; it results from the formation of surface traps owing to the thiol binding [2831]. The PL quenching, which is independent of the MT length, indicates that the number of traps is the same for all linkers, and hence, the number of adsorbed molecules per particle is independent of the length of the linker.…”
Section: Resultsmentioning
confidence: 87%
“…MT linkers were found to quench the PL signal by about 75%, and the quenching was independent of the linker length. This effect is well known for CdSe NPs; it results from the formation of surface traps owing to the thiol binding [2831]. The PL quenching, which is independent of the MT length, indicates that the number of traps is the same for all linkers, and hence, the number of adsorbed molecules per particle is independent of the length of the linker.…”
Section: Resultsmentioning
confidence: 87%
“…Pinning of donor–acceptor energetics constitutes a generic interfacial phenomenon, which has been observed for chemically and morphologically distinct strongly coupled interfaces ( e.g ., QD/oxide systems, QDs/metal contact, bulk semiconductor/semiconductor and semiconductor/liquid interfaces, metal/organic polymer interfaces, , etc. ).…”
Section: Resultsmentioning
confidence: 99%
“…This model is further supported by recent publications that point out to a rather substantial dependence of the electron wavefunction's penetration outside of the CdSe core as function of the core size. 44 It was shown that the probability to nd an electron outside of the core decreases 4-fold when the NC diameter only changes from d ¼ 2.3 nm to d ¼ 2.8 nm. 45 Such strong core size dependence can certainly contribute to the trap-assisted Auger mechanism affecting biexcitonic quantum yield, especially for small core/thin shell nanocrystals.…”
Section: Resultsmentioning
confidence: 99%